Homology - Mac Lane, Saunders (Springer-Verlag, 1995)
Includes bibliographical references (p. [404]-412) and index; Originally published: 3rd corrected printing. Berlin ; New York : Springer-Verlag, 1975, in series: Die Grundlehren der mathematischen Wissenschaften in Einzeldarstellungen mit besonderer Berucksichtigung der Anwendungsgebiete ; Bd. 114